2007
DOI: 10.1186/1744-8069-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Selective microRNAs in Trigeminal Ganglion Neurons Following Inflammatory Muscle Pain

Abstract: Active regulation of gene expression in the nervous system plays an important role in the development and/or maintenance of inflammatory pain. MicroRNA (miRNA) negatively regulates gene expression via posttranscriptional or transcriptional inhibition of specific genes. To explore the possible involvement of miRNA in gene regulation during inflammatory pain, we injected complete Freund's adjuvant (CFA) unilaterally into the rat masseter muscle and quantified changes in neuron-specific mature miRNAs in the trige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 26 publications
1
124
0
1
Order By: Relevance
“…3 from the neuropathic pain study, were compared with previous reports in rodent models for pain investigation. This study is the first report about the association between miRNAs and neuropathic pain in SNL rats, although there was some overlap with previous studies, which focused on the expression changes of miRNAs [27,29,42,44,49].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…3 from the neuropathic pain study, were compared with previous reports in rodent models for pain investigation. This study is the first report about the association between miRNAs and neuropathic pain in SNL rats, although there was some overlap with previous studies, which focused on the expression changes of miRNAs [27,29,42,44,49].…”
Section: Discussionmentioning
confidence: 54%
“…Target prediction algorithms use different parameters to provide candidate target genes for miRNAs. Some of the miRNAs are of special interest concerning their putative targets, so TargetScan was used to identify putative targets and to provide a foundation for functional analyses of neuropathic pain as done in previous reports [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…86 In an inflammatory rat model of CFA-induced muscle pain, several miRNAs including miRs-10a, -29a, -98, -99a, -124a, -134, and -183 were significantly downregulated in neurons of the ipsilateral trigeminal ganglion. 87 This downregulation of specific miRNAs was considered to increase the expression of several "pain-related" proteins and therefore, facilitated the development of inflammation and allodynia. On the other hand, upregulation of miR-155 and miR-223 in the prefrontal cortex has been reported following carrageenan-induced facial inflammation in mice.…”
Section: Activity-dependent Regulation Of M Icrornas In Pain Processingmentioning
confidence: 99%
“…Earlier studies have shown that peripheral inflammation and nerve injury initiate changes in the expression of some miRNAs and Kcna2 AS RNA in DRG [10][11][12][13] and these changes might be responsible for inflammation/nerve injury-induced alterations of some painassociated genes, an increase in DRG neuronal excitability, and pain hypersensitivity [11,13]. Recent evidence indicates that ncRNAs might be the pivotal player in the mechanisms that underlie the development and maintenance of chronic pain.…”
Section: Role Of Mirnas In Chronic Painmentioning
confidence: 99%
“…For instance, in an inflammatory rat model of CFA-induced muscle pain, the authors suggested that this decrease in miRNAs allows for an upregulation of ""pain-related"" proteins that facilitated the development of inflammation and allodynia. [10] …”
Section: Mirnas In Processing Of Painmentioning
confidence: 99%